Acute Limb Ischemia (Ali): An Overview Of Clinical Diagnosis And Treatment - Laksono, Gerardo AK; Erwin, Ferdinand; Tahalele, Paul L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Acute limb ischemia (ALI) is one of vascular emergency. It is defined as a rapid and sudden decrease in limb blood flow due to acute occlusion It is considered to be acute if it occurs within 14 days after the first symptom onset. The incidence of ALI is around 1.5/10.000 people per year. It has reported a mortality rate of 15%-20% in 30 days and high amputation rates 10%-15% if appropriate treatment not administered. The causes of ALI are divided into embolism and thrombosis. Thrombosis can occurred due to atherosclerotic lesion while most cases of embolism are cardiogenic one. Classic features of ALI are known as 6Ps: pain, pallor, paralysis, paraesthesia, pulselessness, poikilothermia. A good history taking and physical examination are needed to assess further treatment needed. Severity of ALI also need to be set based on Rutherford Classification. If the limb was diagnosed as irreversible damage, amputation should be taken as treatment choice without hesitation. ALI can be treated with administered of heparin, endovascular and open surgical. Post treatment follow up also needed to rule out any possible complication such as compartment syndrome and ischemic-reperfusion injury.